Efficacy and safety of sodium-glucose co-transporter 2 inhibition according to left ventricular ejection fraction in DAPA-HF - Dewan, Pooja; Solomon, Scott D; Jhund, Pardeep S; Inzucchi, Silvio E; Køber, Lars; Kosiborod, Mikhail N; Martinez, Felipe A; Ponikowski, Piotr; DeMets, David L; Sabatine, Marc S; Bengtsson, Olof; Sjöstrand, Mikaela; et al. (European journal of heart failure, 2020)
AIMS: The aim of this study was to examine whether left ventricular ejection fraction (LVEF) modified efficacy and safety of dapagliflozin 10 mg compared with placebo in the 4744 patients with LVEF ≤40% randomized in the Dapagliflozin And Prevention of Adverse-outcomes in Heart Failure trial (DAPA-HF). METHODS AND RESULTS: We examined whether LVEF, analysed categorically or continuously, modified the effect of dapagliflozin. The primary efficacy outcome was the composite of a worsening heart failure (HF) event (unplanned HF hospitalization/an urgent HF visit requiring intravenous therapy) or cardiovascular death. Mean LVEF was 31.1% and LVEF categories analysed were: <26% (n = 1143), 26-30% (n = 1018), 31-35% (n = 1187), and >35% (n = 1396). Each 5% decrease in LVEF was associated with a higher risk of the primary outcome [hazard ratio (HR) 1.18; 95% confidence interval (CI) 1.13-1.24]. The benefit of dapagliflozin was consistent across the spectrum of LVEF: the dapagliflozin vs. placebo HR was 0.75 (95% CI 0.59-0.95) for LVEF <26%, 0.75 (0.57-0.98) for LVEF 26-30%, 0.67 (0.51-0.89) for LVEF 31-35%, and 0.83 (0.63-1.09) for LVEF >35% (P for interaction = 0.762). Similarly, the effect of dapagliflozin on the components of the primary endpoint was not modified by baseline LVEF (P for interaction for cardiovascular death = 0.974, and for worsening HF = 0.161). Safety of dapagliflozin was also consistent across the range of LVEF and neither efficacy nor safety were modified by diabetes status. CONCLUSION: Left ventricular ejection fraction was a significant predictor of hospitalization and mortality in patients with HF with reduced ejection fraction but did not modify the beneficial effect of dapagliflozin, overall or separately, in patients with and without diabetes. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov Identifier NCT03036124.
Keywords: Stroke Volume; glukosa; glukosidy; Glucosides; Benzhydryl Compounds; Dapagliflozin; lidé; benzhydrylové sloučeniny; funkce levé komory srdeční; Heart failure; Left ventricular ejection fraction; tepový objem; Sodium-Glucose Transporter 2; Humans; srdeční selhání; sodík; Sodium; Heart Failure; Glucose; transportér 2 pro sodík a glukózu; Ventricular Function, Left